2008
DOI: 10.1073/pnas.0807216105
|View full text |Cite
|
Sign up to set email alerts
|

Competition from below for light and nutrients shifts productivity among tropical species

Abstract: Chance events such as seed dispersal determine the potential composition of plant communities, but the eventual assemblage is determined in large part by subsequent interactions among species. Postcolonization sorting also affects the ultimate composition of communities assembled by people for restoration, horticulture, or conservation. Thus, knowledge of the mechanisms controlling interspecific interactions in plant communities is important for explaining patterns observed in nature and predicting success or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…For example, roots of certain tree species may penetrate into lower mineral soil layers, thereby exploring additional soil volume, or they might specialise on preferential rooting in the organic layer which may not be explored in a comparable intensity by other tree species (e.g. Loreau 1998;Grierson and Adams 1999;Pate and Bell 1999;Ewel and Mazzarino 2008). A higher fine root biomass in multi-species compared to monospecific stands resembles the 'overyielding' phenomenon, which is observed e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, roots of certain tree species may penetrate into lower mineral soil layers, thereby exploring additional soil volume, or they might specialise on preferential rooting in the organic layer which may not be explored in a comparable intensity by other tree species (e.g. Loreau 1998;Grierson and Adams 1999;Pate and Bell 1999;Ewel and Mazzarino 2008). A higher fine root biomass in multi-species compared to monospecific stands resembles the 'overyielding' phenomenon, which is observed e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Menalled et al 1998;Ewel and Mazzarino 2008), a number of authors have emphasized the importance of below-ground complementarity of species for their coexistence and for diversity effects on ecosystem functioning (e.g. Hooper and Vitousek 1997;Loreau 1998;Pate and Bell 1999;Ewel and Mazzarino 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[85] is therefore key to predicting and managing the longterm effects of selective logging and enrichment planting on the structure of the forest and on the services that it provides. Predicting which species provide the most complementary community of species therefore remains a key challenge [43]-especially when multiple forest ecosystem functions are considered. We hope the Sabah Biodiversity Experiment will contribute towards achieving this goal for lowland dipterocarp forests.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, a review of monoculture and polyculture plantations found that mixed species stands tend to be more productive [41]. Apart from these reviews comparing mixedand single-species plantations, the small literature chiefly comprises work from the Neotropics by Ewel and co-worker [42,43] on predicting complementary mixtures of species and a pioneering biodiversity experiment by Potvin and co-workers [44 -46].…”
Section: Introductionmentioning
confidence: 99%
“…Combined, these points suggest that a high density of smaller neighbors correlates positively with crown depth, causing competition for light between overlapping crowns of focal trees and their smaller neighbors (Ewel and Mazzarino 2008). An additional and unrelated indication for a relatively limited role of belowground competition comes from the above mentioned allometry study: Averaged across 260 saplings of 12 species, the projected root area was 3.0 (±0.2 SE) times smaller than the projected crown area (M. van Breugel unpublished data).…”
Section: Symmetry Does Not Necessarily Imply Belowground Competitionmentioning
confidence: 99%